Investigation of Lactobacillus spp. bacteria in infants consuming breast milk and formula and determination of some probiotic characters - Muslu Çağal, Tuğçe; Kıray, Esin; Kariptaş, Ergin (The European Research Journal, 2023)
Objectives: It was aimed to investigate some probiotic properties of Lactic Acid Bacteria (LAB) isolated from stool samples taken from 45 healthy 0-4 month old babies, who did not take antibiotics or probiotic supplements in the last 3 months, and who did not have any health problems. Methods: Six different species were obtained from 21 isolates selected by the method of Mass Spectrometry (MALDI-TOF MS). Results: The most common strain was Lactobacillus rhamnosus with a rate of 59%, followed by Lactobacillus paracasei with a rate of 13.6%. Vancomycin, tetracycline, gentamicin, netilmicin, tobramycin, penicillin, ampicillin, teicoplanin and amikacin antibiotics were used to evaluate the antimicrobial activities of the strains. In our study, while all strains were resistant to the antibiotic amikacin, they were sensitive to tetracycline, penicillin, gentamicin, netilmicin, teicoplanin, vancomycin, ampicillin and tobramycin antibiotics. In the evaluation of the antagonistic activities of LAB, 6 different pathogens (Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, Bacillus subtilis ATCC 6633, S. aureus ATCC 25923, Candida albicans ATCC 10231, Listeria monocytogenes ATCC 19111) were used and it was determined that the strains showed antimicrobial effects on all pathogenic microorganisms. Cholesterol assimilation abilities, T21 and T22 strains achieved the highest cholesterol assimilation rate of 39.1%. Conclusions: It is thought that most of the isolated strains have probiotic potential, and especially Lactobacillus gasseri T21 and L. paracasei T22 strains may be probiotic strains that can be used in the production of preparations alone or together with other Lactobacillus strains.